2017
DOI: 10.3390/ijms18112331
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-Rich Dry Common Beans (Phaseolus vulgaris L.) and Their Health Benefits

Abstract: Polyphenols are plant metabolites with potent anti-oxidant properties, which help to reduce the effects of oxidative stress-induced dreaded diseases. The evidence demonstrated that dietary polyphenols are of emerging increasing scientific interest due to their role in the prevention of degenerative diseases in humans. Possible health beneficial effects of polyphenols are based on the human consumption and their bioavailability. Common beans (Phaseolus vulgaris L.) are a greater source of polyphenolic compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
163
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(175 citation statements)
references
References 159 publications
(145 reference statements)
5
163
1
6
Order By: Relevance
“…Another noteworthy point is that according to FRAP and ABTS methods, the antioxidant activity of most pigmented bean coats is higher than most common fruits and vegetables (Gan et al., ). Furthermore, not only the in vitro studies but animal studies have also confirmed that common beans possess antioxidant activity, as measured in various biochemical parameters such as thiobarbituric acid reactive substances, hydroperoxides, glutathione, glutathione reductase, glutathione S‐transferase, glutathione peroxidase, and catalase (Ganesan & Xu, ). Xu and Chang () reported that raw pinto and black beans ( Phaseolus vulgaris L.) exhibited cellular antioxidant activities in dose‐dependent manners.…”
Section: Antioxidant Activitymentioning
confidence: 91%
“…Another noteworthy point is that according to FRAP and ABTS methods, the antioxidant activity of most pigmented bean coats is higher than most common fruits and vegetables (Gan et al., ). Furthermore, not only the in vitro studies but animal studies have also confirmed that common beans possess antioxidant activity, as measured in various biochemical parameters such as thiobarbituric acid reactive substances, hydroperoxides, glutathione, glutathione reductase, glutathione S‐transferase, glutathione peroxidase, and catalase (Ganesan & Xu, ). Xu and Chang () reported that raw pinto and black beans ( Phaseolus vulgaris L.) exhibited cellular antioxidant activities in dose‐dependent manners.…”
Section: Antioxidant Activitymentioning
confidence: 91%
“…Plant antimicrobial secondary metabolites are generally categorized into three broad classes, namely phenolic compounds, terpenes, and alkaloids. Numerous studies have shown that the antimicrobial activity of the plant extracts and their active compounds have the following potential: to promote cell wall disruption and lysis, induce reactive oxygen species production, inhibit biofilm formation, inhibit cell wall construction, inhibit microbial DNA replication, inhibit energy synthesis, and inhibit bacterial toxins to the host [75,85,[105][106][107][108][109]. In addition, these compounds may prevent antibacterial resistance as well as synergetics to antibiotics, which can ultimately kill pathogenic organisms (Figure 1).…”
Section: Mechanism Of Actions Of Antibacterial Bioactive Compoundsmentioning
confidence: 99%
“…These potential aromatic compounds are usually targeted to microbial cell surface adhesins, membrane-bound polypeptides, enzymes, and eventually lysis of the microbes [111]. Flavonoids are hydroxylated phenolic substances which are also able to complex with bacterial cell walls and disrupt microbial membranes [75,105]. Highly active flavonoids, quercetin (1), rutin (2), naringenin (3), sophoraflavanone (4), tiliroside (5) and 2, 4, 6-trihydroxy-30-methyl chalcone (6) ( Figure 2) decreased lipid bilayer thickness and fluidity levels and increased membrane permeability, supporting the leaking of intracellular protein and ions in S. aureus and S. mutans [112,113].…”
Section: Promote Cell Wall Disruption and Lysismentioning
confidence: 99%
“…Phaseolus vulgaris L, also known as the common bean is an herbaceous annual flowering plant. Different types of common beans that are cultivated for edible purposes are navy beans, kidney beans, red beans, black beans, pinto beans and can berry beans [1]. They belong to the Fabaceae or leguminaceae family that is widely distributed in all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports concerning bean intake and reduced risk of cardiovascular disease, diabetes mellitus, obesity, cancer and diseases of the gastrointestinal tract [1,3,4]. These potential health aspects of beans have *Corresponding Author Email: aliamoghadamnia@gmail.com (A.…”
Section: Introductionmentioning
confidence: 99%